Gain enhancement of microstrip patch antenna / Azwan Mohd Yusoff - Mohd Yusoff, Azwan (2012)
In this paper , a 2x1 microstrip patch antenna array design is presented. This antenna is designed at 5.8GHz on FR4 substrate with dielectric constant at 4.7 and 0.0025 tangent loss. The simulation start with single patch antenna and followed by the 2x1 antenna array using T-junction power divider. Different spacing between patches will be simulated in order to investigate the antenna performance in term of gain and sidelobes. This project was succesfully displayed the grating lobes start to appear at certain spacing distance. The overall of the project concludes that during simulation design, the spacing distance of d=X/2 was the best spacing distance. However, during the measurement procedure, the Sn(dB) of d=k/2 not exceed the -lOdB requirement